Conformation and Counterion Distribution of Polyelectrolyte in Solution as Viewed from Dielectric Approach - Zhao, Kong-Shuang (Chinese journal of polymer science, 2024)
Polyelectrolyte solutions are more variable than uncharged macromolecule due to electrical interaction between charged molecules and surrounding counterions. Therefore, the subject of polyelectrolyte solutions has attracted a wide range of interests in both basic and applied research, and has also been extensively explored. However, the understanding of the molecular dynamics and conformation of polyelectrolytes in solution remains to be deepened, and universal consensus on some key issues have not been reached. Many methods have contributed to solving the above problems in different ways, including dielectric relaxation spectroscopy (DRS). In this perspective, we briefly reviewed the history of dielectric spectroscopic research on polyelectrolyte solution, with emphasis on summarizing our efforts. In particular, we expound the characteristics of DRS and its ability to obtain the internal information of the system of interest. Finally, we evaluate the advantages and limitations of the dielectric method and discussed future prospects of this field.